Palm oil deoxygenation with glycerol as a hydrogen donor for renewable fuel production using nickel-molybdenum catalysts: The effect of support - Nitchakul Hongloi; Tawsif Rahman; Farshad Feyzbar-Khalkhali-Nejad; Chaiwat Prapainainar; Peerawat Wongsurakul; Emmanuel Aransiola; Lihua Zhang; Pascal Bargiela; Jonas Baltrusaitis; Paweena Prapainainar; Sushil Adhikari (Fuel Processing Technology)
Palm oil, one of the most widely used vegetable oils, offers significant potential as a sustainable feedstock for biofuel production. This study explores the deoxygenation of palm oil using glycerol as a hydrogen donor, with nickel‑molybdenum (NiMo) catalysts supported on commercial alumina (Al2O3), and zeolite (HZSM-5) comparing with self-prepared zirconia (ZrO2). The catalysts were synthesized via incipient wetness impregnation and evaluated for their performance in biofuel production. NiMo/Al2O3 exhibited the lowest oxygen removal efficiency (68.5 %), while NiMo/HZSM-5 achieved a higher oxygen removal (74.3 %) but also demonstrated the highest coke formation. The type of support material influenced the resulting biofuel range, with NiMo/HZSM-5 and NiMo/ZrO2 favoring jet fuel production, whereas NiMo/Al2O3 was more suitable for diesel production. Notably, NiMo/ZrO2 exhibited the highest performance in palm oil deoxygenation while minimizing coke formation. These findings highlight NiMo/ZrO2 as a promising catalyst for efficient and stable biofuel production, with the support material significantly influencing product yield and fuel quality.